Progression of coronary atherosclerosis in stable patients with ultrasonic features of high-risk plaques. (1st September 2014) - Kataoka, Yu; Wolski, Kathy; Balog, Craig; Uno, Kiyoko; Puri, Rishi; Tuzcu, E. Murat; Nissen, Steven E.; Nicholls, Stephen J.
Abstract: Aim: Large plaque burden, expansive vascular remodelling, and spotty calcification have been considered as important morphologies of high-risk plaques causing acute coronary events. Although non-occlusive rupture of high-risk plaques has been proposed as a mechanism for disease progression in post-mortem studies, the natural history of coronary atherosclerosis in stable patients with high-risk plaques has not been fully elucidated. We sought to evaluate coronary atheroma progression in stable patients with greyscale intravascular ultrasound (IVUS)-derived high-risk plaques. Methods and results: We analysed 4477 patients with stable coronary artery disease underwent serial greyscale IVUS imaging in eight clinical trials. We compared volumetric intravascular ultrasound (IVUS) data in the non-culprit segments between patients with and without high-risk plaques, defined as the combination of per cent atheroma volume (PAV) >63%, positive remodelling and spotty calcification. High-risk plaques were observed in 201 (4.5%) of patients. Patients with high-risk plaques exhibited a greater PAV (47.1 ± 8.4 vs. 37.7 ± 8.7%, P < 0.001) at baseline. On serial evaluation, however, regression of PAV (−0.26 ± 0.39 vs. 0.24 ± 0.32%, P = 0.03) was observed. In patients with high-risk plaques, the non-statin use was associated with the accelerated atheroma progression, whereas atheroma regression was observed under statin therapy (change in PAV: 1.87 ± 0.68% vs. −0.83 ± 0.53%, P = 0.01). Conclusions: Patients with high-risk plaques exhibit extensive atheroma burden, which is modifiable with anti-atherosclerotic therapies. These findings underscore risk modification using a statin in patients with high-risk plaques.